Swot analysis of thrifting business on tik-tok social media reviewed from islamic business perspective (case study on tik-tok account @kacestore) - Nurhayati, Nurhayati; Rosilawati, Weny; Selvina, Mia; Riski, Yogi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Tiktok Shop social media is an online shopping platform that prioritizes user convenience, however, in practice there are some unscrupulous used clothing sellers on tik-tok who have unclear implementation, such as about the quality of the clothes sold and the original form of the clothes they sell.This study investigates the implementation of SWOT in the used goods business on Tiktok social media with an Islamic business approach. Tiktok Shop has become the main platform for online shopping with an emphasis on user convenience, but it also faces challenges related to the lack of clarity in the sale of used clothing, such as the quality and origin of products that are often imported and potentially harmful to health. The purpose of this study is to evaluate the strengths, weaknesses, opportunities, and threats in buying and selling practices on the Tiktok kacestore account, using qualitative research methods through field research. The sample consisted of 100 participants who were followers of the account, selected using a stratified random sampling technique. The results of questionnaire and interview analysis show that the kacestore business actors have successfully applied the principles of buying and selling in accordance with Islamic business values, reflecting the traits of Rosulullah SAW such as siddiq, amanah, tabligh, and fathonah in their operational practices. The conclusion of this study illustrates that the implementation of SWOT in the second-hand goods business in Tiktok can be an effective foundation for developing sustainable and ethical business strategies, and have applied the characteristics of Rosulullah SAW consisting of siddiq, amanah, tabligh, fathonah.